Restoration of mismatch repair to nuclear extracts of H6 colorectal tumor cells by a heterodimer of human MutL homologs. - Li, G M (1995)
Hypermutable H6 colorectal tumor cells are defective in strand-specific mismatch repair and bear defects in both alleles of the hMLH1 gene. We have purified to near homogeneity an activity from HeLa cells that complements H6 nuclear extracts to restore repair proficiency on a set of heteroduplex DNAs representing the eight base-base mismatches as well as a number of slipped-strand, insertion/deletion mispairs. This activity behaves as a single species during fractionation and copurifies with proteins of 85 and 110 kDa. Microsequence analysis demonstrated both of these proteins to be homologs of bacterial MutL, with the former corresponding to the hMLH1 product and the latter to the product of hPMS2 or a closely related gene. The 1:1 molar stoichiometry of the two polypeptides and their hydrodynamic behavior indicate formation of a heterodimer, which we have designated hMutL alpha. These observations indicate that interactions between members of the family of human MutL homologs may be restricted.